Evaluation of antioxidant capacity in different food matrices through differential pulse voltammetry and its correlation with spectrophotometric methods (2023)
ABSTRACT: Diferential pulse voltammetry (DPV) and spectrophotometric methods were used to evaluate the antioxidant capacity (AC) in strawberry and orange juice, soluble cofee, rosemary extract, red wine, and sparkling white wine. The AC through spectrophotometric methods showed the following trend in solid foods, cofee>rosemary extract, and red wine>strawberry juice>orange juice>sparkling white wine in liquid samples. Charge measurements by DPV, presented in equivalent units of Trolox and gallic acid, showed the same trend in liquid samples; however, for solid samples, the AC of rosemary extract was greater than that of cofee. The charge expressed in equivalent units showed a high, positive, and signifcant correlation (p<0.001) with total phenols (0.7919), FRAP (0.8875), and ABTS (0.8366). The proposed electrochemical technique proves to be a fast, reliable, and environmentally friendly alternative or complement to evaluate antioxidant capacity in food, which is not afected by the turbidity or color of the samples.